Financial accounting demystified - Berry, Leonard Eugene (McGraw-Hill "Demystified" series, 2011)
Overview: The simple solution to complex accounting. You don't need a genius IQ to ace your financial accounting curriculum. The only prerequisites are a little discipline and a comprehensive tutorial devoid of confusing jargon. Financial Accounting DeMYSTiFieD presents all the concepts and skills you need, in a language you understand. Designed to let you learn at your own pace, it explains all the rules for preparing and reporting accounting information to parties outside an organization. Then, you'll get details on basic financial accounting concepts, valuing inventories, accounting methods, stockholder's equity, receivables, and more. Featuring end-of-chapter quizzes and a final exam, Financial Accounting DeMYSTiFieD teaches you the ins and outs of financial accounting in no time at all! This fast and easy guide offers: Expert coverage of financial statements, cash and short-term investments, receivables, cash flows, liabilities; Tips, techniques, and insights that drive home key financial accounting principles and theories; Hundreds of worked-out examples, chapter-ending quizzes, and a final exam to reinforce learning and pinpoint weaknesses; Specific recommendations if you're having difficulty with certain subtopics. Simple enough for a beginner, but challenging enough for an advanced student, Financial Accounting DeMYSTiFieD is a shortcut to developing a working knowledge of accounting practices